Parallel Serpent under MorphoSys - Damaj, Issam (2011)
The use of cryptographic algorithms within critical applications, such as banking and military, requires efficient hardware implementations. With the emergence of reconfigurable computing architectures, such modern and capable systems became the target of many applications including cryptography. This paper presents parallel reconfigurable hardware implementations of the Serpent (AES Finalist) cryptographic algorithm. Currently, Serpent is well known to be a simple but very strong encryption algorithm. The used system is the MorphoSys dynamically reconfigurable computer.Different designs for the Serpent corresponding to different degrees of parallelism are presented.Moreover, implementation, realization, and performance analysis and evaluation of the mapped designs are included. The Serpent algorithm is shown to have increased performance when mapped on MorphoSys.